Digital Marketing Melalui Sosial Media Instagram Pada Toko Bunga Youwant_Bouquet - Damayanti, Desi; Muis, Indra (JURNAL MAHASISWA BINA INSANI, 2023)
The rapid development of technology and communication affects all areas of human life. This also affects the marketing system at the Youwant_Bouquet flower shop. The purpose of this study was to find out how to implement digital marketing via Instagram at youwantbouquet flower shops. The research method used is qualitative by conducting direct interviews with owners and employees. The results of the digital implementation through Instagram social media implemented by Toko Youwant_Bouquet take advantage of Instagram's features by creating interesting content. Youwant_Bouquet flower shop uses Instagram Feeds to upload photos or videos as an online catalog. Instagram Stories are used to interact with consumers and also upload short videos of product creation. instagram reels the contents of the content uploaded on these reels are in the form of a compilation of videos of the manufacturing process, finished products, or store displays. In carrying out digital marketing through Instagram social media, the Youwant_Bouquet flower shop experienced a problem, namely the lack of extensive promotion carried out, the Youwant_Bouquet flower shop only used Instagram social media. The solution to this problem is to create TikTok and Shopee social media accounts to expand marketing.